A Hemodynamic Study to assess response, tolerance and dose optimization of Carvedilol in Child Class A patients with Portal Hypertension - Nazir, Shaheen; Ahmed, Zeeshan; Mohamad, Muzzafer; Ahmad, Afaq; Ahmed, Wasim; Haq, Inaam -ul-; Hussain, Altaf (Asian Journal of Medical Sciences, 2021)
Background: Carvedilol has an established role in Chronic Liver disease (CLD) associated Portal Hypertension, however its role in specific subclasses of CLD has not been studied, neither the factors leading to non-response thereby predisposing such patients to variceal bleed with empiric therapy. Aims and Objectives: The purpose of this study was. 1. To evaluate the hemodynamic response to Carvedilol and optimum dosage in patients of CTP Class A Cirrhosis. 2. To determine any clinical variables that would help in differentiating responders from non-responders. Materials and Methods: In forty-three consecutive patients of chronic liver disease Child Turcotte Pugh (CTP) Class A with esophageal varices, Hepatic Venous Pressure Gradient (HVPG) was measured at baseline, 90 minutes after initial administration of 12.5 mg of Carvedilol and after 3 months of dose optimization. Results: Twenty-one (48.8%) patients demonstrated Acute Response and after dose optimization Chronic Response was seen in 29 (67.4%) patients with additional 8 (18.6%) patients responding to dose optimization. Fourteen (32.55%) patients failed to show any response. Low pre-drug Cardiac Output (CO), High pre-drug mean arterial pressure (MAP), more than 2.5mmHg drop in HVPG acutely, higher dose toleration of more than 18.5mg and lower change in HR predicted response. Conclusion: Patients with CTP Class A Cirrhosis with Portal Hypertension and Esophageal Varices tolerate Carvedilol well and nearly two-thirds show hemodynamic response when dose is optimized over a period of time, including patients who initially show no acute response. Nearly one-third of patients show no response even after dose optimization.